Idiopathic choroidal neovascularization in children - Krzyżanowska-Berkowska, Patrycja; Agopsowicz-Spławska, Karolina; Barć, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Idiopathic choroidal neovascularization (CNV) in children is a rare, but important cause of visual impairment. Purpose of this paper is to report one year clinical observation of 4 children with idiopathic choroidal neovascularization. Authors present 4 cases of CNV in boys at 6-13 years old, with unilateral visual deterioration onset. All cases were diagnosed as idiopathic ones after pediatric and ophthalmological examination including fundus color photographs and optical coherence tomography (OCT) in all cases, fluorescein angiography (FA) in 2 cases, as well as laboratory tests to exclude the systemic diseases. All cases were left untreated. This presentation discusses therapeutic management according to the argon laser therapy, photodynamic therapy, submacular surgery and intravitreal injection of anti-VEGF.